HUBUNGAN KARAKTERISTIK DAN PENGETAHUAN REMAJA TENTANG ROKOK DENGAN PERILAKU MEROKOK REMAJA DI KULONPROGO YOGYAKARTA - Sujono Riyadi; Dwi yati; Afi Lutfiyati (Wiraraja Medika : Jurnal Kesehatan, 2018)
Smoking is a habit that can provide pleasure for smokers themselves, but on the otherhand can also cause negative impacts for the smokers themselves and for those around them. Aperson exposed to secondhand smoke (passive smokers) for eight hours is proportional to directsmoking of 20 cigarettes per day. The purpose of this research is to know the correlation ofadolescent characteristic and knowledge about cigarette with teenage smoking behavior inKulonprogo YogyakartaThis research is quantitative by using analytic survey method with cross sectionalapproach, as many as 160 teenagers who smoke in Kulonprogo Regency Yogyakarta. Datacollection by using questionnaire and analyzed by using Pearson correlation statistic test.The results showed that the correlation coefficient between adolescent knowledge aboutsmoking with teen smoking behavior in Kulonprogo Yogyakarta (-0.205). The correlation coefficientbetween adolescent age and teenage smoking behavior in Kulonprogo Yogyakarta amounted to(0,472) and correlation coefficient between adolescent pocket money and teenage smokingbehavior in Kulonprogo Yogyakarta (0,412).There is a relationship between adolescent age with teenage smoking behavior inKulonprogo Yogyakarta. There is a relationship between adolescent pocket money and teenagesmoking behavior in Kulonprogo Yogyakarta. The higher the adolescent knowledge aboutcigarettes then the behavior of adolescent smoking in Kulonprogo Yogyakarta will be lower.